Blockchain and Decentralized Finance (DeFi): Challenges and Future Potential - Anish Naidu Basa (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This paper explores decentralized finance (DeFi), a fast-growing area powered by blockchain technology that offers a new alternative to traditional financial systems. DeFi removes the need for intermediaries like banks, making transactions more transparent, accessible, and often cheaper. This shift not only reduces costs but also helps improve financial access, particularly for people who are underserved by traditional banking systems. Key elements of DeFi, such as smart contracts and oracles, play a central role in automating processes and enabling peer-to-peer exchanges without needing middlemen. Despite its advantages, DeFi faces several challenges. Smart contracts can have security vulnerabilities, oracles may not always provide accurate data, and there is little consumer protection in place, which raises risks for users. Furthermore, DeFi’s decentralized and often anonymous structure creates regulatory difficulties, especially when it comes to complying with anti-money laundering (AML) and know-your-customer (KYC) standards, which are crucial for ensuring financial safety and preventing illegal activities. This paper examines these issues and proposes potential solutions, such as decentralized oracle networks, regulatory tools embedded within DeFi platforms, and improved scalability techniques. These solutions aim to enhance DeFi’s security while maintaining its core decentralized benefits. The paper concludes by discussing the future of DeFi, stressing the importance of balanced regulations that protect users without stifling innovation. Ultimately, DeFi holds the potential to reshape global finance, making it more inclusive, efficient, and accessible.